Investment in wholesale stores and shops and technological equipment development - Svetikas, Antanas (Business: Theory and Practice, 2007)
When we choose a strategy, which is based on the maintenance of existing position (even if not the best, but stable and available), it is most important to maintain good relations with wholesellers. It is also nessesary to eliminate possible activity of rivals. In this case cooperators have to reduce their part in the market. None of these strategies is better or worse than the other, but under some conditions, one is more suitable, and under other conditions, the other. When we choose a strategy, firstly the possibilities of cooperation, selling of production and conditions of competition should be mentioned. Enterprise strategies are planned differently. Mostly enterprise workers’ experience, creative and intellectual powers are used. In other cases the consultants, who have more experience and information, and who are more objective in evaluating strong and weak parts of enterprise, are applied to.